Theoretical and Experimental Studies of the Developing Turbulent Non-Newtonian Flow in a Pipe - Embaby, M.H.; Verba, A. (Engineering Transactions, 1982)
A theoretical analysis is given for the developing turbulent non-Newtonian flow in a circular or a square cross section pipe. An experimental study on a square cross section pipe, using aqueous solutions of carboxymethyl cellulose as the non-Newtonian fluids, was carried out. Predictions of the pressure distribution and the critical Reynolds number are presented.